To prove that the expressions \((x - 5)(x + 3)\) and \(2x^2 - x^2 - 2x - 20 + 5\) are equivalent, we can simplify both expressions and show that they are equal.
Work for Expression 1:
- Apply the Distributive Property (FOIL method): \[ (x - 5)(x + 3) = x(x) + x(3) - 5(x) - 5(3) \] \[ = x^2 + 3x - 5x - 15 \] \[ = x^2 - 2x - 15 \]
Work for Expression 2:
- Simplify the expression: Combine like terms in \(2x^2 - x^2 - 2x - 20 + 5\): \[ = (2x^2 - x^2) - 2x - 20 + 5 \] \[ = x^2 - 2x - 15 \]
Conclusion:
Both expressions simplify to \(x^2 - 2x - 15\), thus proving that \((x - 5)(x + 3)\) is equivalent to \(2x^2 - x^2 - 2x - 20 + 5\) because they yield the same polynomial when fully simplified.